Dynamical regularities of US equities opening and closing auctions - Challet, D; Gourianov, N (World Scientific Publishing Company, 2019)
We first investigate the evolution of opening and closing auction volumes of US equities along the years. We then report the dynamical properties of pre-auction periods: the indicative match price is strongly mean-reverting because the imbalance is; the final auction price reacts to a single auction order placement or cancellation in markedly different ways in the opening and closing auctions when computed conditionally on imbalance-improving or worsening events; the indicative price reverts towards the mid-price of the regular limit order book but is not especially bound to the spread.